2023
DOI: 10.1182/blood.2023019663
|View full text |Cite
|
Sign up to set email alerts
|

Silent cerebral infarction during immune TTP remission - prevalence, predictors, and impact on cognition

Abstract: Immune TTP (iTTP) survivors have increased risk of cardiovascular disease including stroke, and report persistent cognitive difficulties during remission. We conducted this prospective study of iTTP survivors in clinical remission to determine the prevalence of silent cerebral infarction (SCI), defined as magnetic resonance imaging (MRI) evidence of brain infarction without corresponding overt neuro-deficits, during clinical remission. We also tested the hypothesis that SCI is associated with cognitive impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Recent data show that patients with iTTP in remission might experience cognitive symptoms and are also susceptible to TIA and stroke. These findings imply that severe deficiency of ADAMTS13 is a risk for cognitive impairment [39]. This suggests that prophylactic treatment may be appropriate for all patients with hTTP.…”
Section: Management Strategiesmentioning
confidence: 84%
See 1 more Smart Citation
“…Recent data show that patients with iTTP in remission might experience cognitive symptoms and are also susceptible to TIA and stroke. These findings imply that severe deficiency of ADAMTS13 is a risk for cognitive impairment [39]. This suggests that prophylactic treatment may be appropriate for all patients with hTTP.…”
Section: Management Strategiesmentioning
confidence: 84%
“…Increased risk for stroke in patients with iTTP in remission but with low ADAMTS13 activity was recently confirmed. Among 36 patients with iTTP in clinical remission, patients with lower ADAMTS13 activity had higher risk for stroke [39].…”
Section: Ittpmentioning
confidence: 96%
“…Most recently, a study reported that in a prospectively enrolled cohort of iTTP survivors, 50% demonstrated silent cerebral infarction, which is defined as magnetic resonance imaging (MRI) evidence of brain ischemic infarction without a corresponding neuro-deficit [ 35 ]. Silent cerebral infarction was strongly associated with cognitive impairment, including both major and mild cognitive impairment [ 35 ].…”
Section: Cardiovascular Disease Burden In Chronic Ittpmentioning
confidence: 99%
“…Most recently, a study reported that in a prospectively enrolled cohort of iTTP survivors, 50% demonstrated silent cerebral infarction, which is defined as magnetic resonance imaging (MRI) evidence of brain ischemic infarction without a corresponding neuro-deficit [ 35 ]. Silent cerebral infarction was strongly associated with cognitive impairment, including both major and mild cognitive impairment [ 35 ]. Given that silent cerebral infarctions are a risk factor for both cognitive impairment [ 36 ] and stroke [ 37 ] in the general population, it is likely that silent cerebral infarction also contributes to neurocognitive deficits that are a common complaint in TTP survivors (60–80%) [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Cardiovascular Disease Burden In Chronic Ittpmentioning
confidence: 99%
See 1 more Smart Citation